2021
DOI: 10.2516/ogst/2020097
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic methane hydrate production stimulated with CO2 and N2

Abstract: The cyclic methane hydrate production method was proposed with CO2 and N2 mixture stimulation. The cyclic production model was established based on actual hydrate reservoir parameters, accordingly, the production characteristics were analyzed, and a sensitivity analysis was conducted. The results show the following: (1) The depressurization mechanism is dominant in the cyclic production. CH4 production and CH4 hydrate dissociation can be greatly enhanced because the cyclic process can effectively reduce the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… P – T phase equilibrium curves of CH 4 and N 2 hydrates 35 [reprinted (adapted or reprinted in part) according to Creative Commons Attribution License from Xia, Z.; Hou, J.; Wang, X.; Dai, X.; and Liu, M. Cyclic MH Production Stimulated with CO 2 and N 2 . Oil &Gas Science and Technology — Revue D’IFP Energies Nouvelles 2021 , 76 , 14.…”
Section: Model Establishmentmentioning
confidence: 99%
See 2 more Smart Citations
“… P – T phase equilibrium curves of CH 4 and N 2 hydrates 35 [reprinted (adapted or reprinted in part) according to Creative Commons Attribution License from Xia, Z.; Hou, J.; Wang, X.; Dai, X.; and Liu, M. Cyclic MH Production Stimulated with CO 2 and N 2 . Oil &Gas Science and Technology — Revue D’IFP Energies Nouvelles 2021 , 76 , 14.…”
Section: Model Establishmentmentioning
confidence: 99%
“…Yasue et al 34 16 depressurization, thermal stimulation Alaska North Slope 17 CO 2 −N 2 gas mixture injection Eastern Nankai Trough 18,19 depressurization South China Sea 20,21 depressurization concluded that a higher N 2 concentration could enhance CH 4 production. In addition, our previous study 35 showed that pure N 2 injection was more effective than CO 2 /N 2 mixed gas from the perspective of CH 4 production.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation